Analysis of Legal Protection of Children in Cases of Underage Divorce in Indramayu - Sarib, Suprijati; Lubis, Arief Fahmi; Hasibuan, Kalijunjung (Westscience Press, 2023)
This research investigates the legal protection of children in underage divorce cases in the context of Indramayu, Indonesia. Using a mixed methods approach, the research analyzed the legal framework, reviewed existing literature, and gathered insights through surveys with legal professionals, social workers, and individuals who have direct experience in underage divorce cases. The findings revealed nuances in the legal landscape, challenges in implementation, and the importance of cultural sensitivity. Recommendations emphasize alignment of legal standards, improved support services, interdisciplinary collaboration, compassionate legal processes, and community engagement.